European natural gas prices - Rogers, H (Oxford Institute for Energy Studies, 2009)
There are two types of gas sold in Europe. Their appearance and physical characteristics are identical; the only difference is the way in which they are priced. This summer, pipeline gas from Russia and North Africa was selling at around $8/mmbtu, while traded or 'spot' gas in the UK was selling for around $3/mmbtu. The fact that the same commodity should be the subject of such extreme price variation raises three questions: How has the market architecture developed to allow such disparities to arise? What are the forces currently applying stresses to this structure? Is such a system sustainable?